(untitled) (Nigerian Journal of Technology, 2022)
The research explored ways in which power supplied in Onitsha distribution line network would be enhanced using distributed generation. The problem of insufficient power supply in densely populated metropolis which is characterised by frequent load shedding was solved using optimal placement and sizing of multiple distributed generation. A gas plant was optimally placed at 33 kV injection substations at Awada and General Cotton Mill (GCM). The generators were optimally placed using voltage sensitivity index factor, while their optimum capacities were sized using step method. Simulations were done by power system analysis toolbox (PSAT) 2.1.11 simulation tool in MATLAB 2018a environment and the result of the findings revealed that 32 buses out of 34 buses were violated. The result of the simulation also showed that the optimal operating power output of the generators at Awada and GCM of 12.5 MW and 2.5 MW respectively could only clear 29 out of the 32 bus voltage violations. Overloading of Fegge injection substation transformer was identified as the cause and its upgrade from 7.5 MVA to 15.0 MVA cleared all the voltage violations. The system active loss and reactive loss were 1.82 MW and 35.03 MVar and the research was able to reduce them by 23.30% and 23.80% respectively. The statutory bus voltage limits of ±5% and the requirement that distributed generators installed must be less than the maximum demanded had been achieved in the research. The power supply in Onitsha distribution network was enhanced using distribution generations and the usage of optimal placement and sizing of multiple distributed generation is therefore recommended for problematic distribution networks not only for loss reduction also for better performance.